1996
DOI: 10.1016/s0022-5347(01)66050-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weights and Isoelectric Points of Sperm Antigens Relevant to Autoimmune Infertility in Men

Abstract: Significant antibody responses to C1 inhibitor-like protein and calmodulin were noted in autoimmune men. Both of these proteins may be of testicular origin and these autoimmune responses may be highly relevant to infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our previous studies have revealed that infertile patients have antibodies against C 1 -1NH-L protein on sperm. 3 The present study has identified complement regulatory proteins such as C1 -INH, DAF (CD55), MCP (CD46), and HRF (CD59) in sperm membrane lysates that may be the targets for sperm antibodies. Because the amount of sample used in each well was the same, the density of the bands suggests that C l -INH is the major complement regulatory protein on the sperm surface (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our previous studies have revealed that infertile patients have antibodies against C 1 -1NH-L protein on sperm. 3 The present study has identified complement regulatory proteins such as C1 -INH, DAF (CD55), MCP (CD46), and HRF (CD59) in sperm membrane lysates that may be the targets for sperm antibodies. Because the amount of sample used in each well was the same, the density of the bands suggests that C l -INH is the major complement regulatory protein on the sperm surface (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…* Infertile men and their wives with cytotoxic sperm antibodies have autoantibodies to spermassociated C1-INH-like proteins (C1-INH-L). 3 Seminal plasma C1 inhibitor (Cl-INH) levels in these men were significantly lower than those in fertile control subject^.^ Our hypothesis is that lack of these proteins on the sperm surface be-cause of the action of auto-antibodies to these proteins may result in a loss of spermatozoa in both male and female reproductive tracts. These molecules on the sperm surface may have other biological functions as well, in addition to their ability to regulate complement activity, such as sperm motility.s…”
Section: Introductionmentioning
confidence: 88%
“…The phage display technology seems to be a powerful tool to identify immunoinfertility-associated sperm antigens, both the peptide moieties as well as the carbohydrate mimetics of the peptide epitopes. In the past, several proteomic methodologies, immunologic techniques, and the two-dimensional gel electrophoresis/matrix-assisted laser desorption mass spectrometry have been used to delineate molecular identities of the sperm antigens that are involved in antisperm antibody-mediated immunoinfertility (Auer et al, 1995;Pillai et al, 1996;Shetty et al, 1999). Although a few interesting leads have been found, very few sperm antigens have been identified that are indeed involved in immunoinfertility.…”
Section: Sperm Antigensmentioning
confidence: 99%
“…In most cases, however, the reactions of sperm antigens with control sera from fertile individuals were not described, so the functional relevance of these antigens in fertility remains unclear. Furthermore, most of the earlier studies used unidimensional gel electrophoresis for the separation of sperm proteins [22,25,[31][32][33][34][35]. In the present study, we adopted high-resolution two-dimensional (2D) electrophoresis with separation of sperm antigens in the first dimension by either isoelectric focusing (IEF) or nonequilibrium pH gradient electrophoresis (NEPHGE) to screen a range of acidic and basic proteins, followed by PAGE and a sensitive Western blotting method.…”
Section: Introductionmentioning
confidence: 99%